Respons Planlet Stevia (Stevia rebaudiana) terhadap Penambahan berbagai Konsentrasi Thidiazuron (TDZ) dan Naphthalene Acetic Acid (NAA) secara in Vitro - Dimas, Muhammad; Indrawati, Wiwik; Supriyatdi, Dedi (Jurnal Agro Industri Perkebunan, 2023)
Stevia can be developed by vegetative and generative propagation, while the generative propagation of stevia can be done through seeds. Conventional provision of seeds or seedlings has a low success rate. Propagation via tissue culture is faster, produces more seeds, and is identical to the parent, so the plants’ quality is expected. Plant growth regulator (PGR) often used for tissue culture is type auxins, cytokinins and gibberellins. The function of auxin and cytokinin for division cells, cell elongation, cell differentiation and organ formation. This research aims to get the concentration as well as the best combination for the growth of stevia plants against the administration of thidiazuron (TDZ) and naphthalene acetic acid (NAA). Research carried out by the randomised block design (RBD) factorial pattern consisting of two factors: TDZ and NAA. The first factor is TDZ concentration consisting of three levels: 0 mg.l-1 (T0), 1 mg.l-1 (T1), and 2 mg. l-1 (T2). The second factor is NAA concentration, which consists of three levels: 0 mg.l-1 (N0), 1 mg.l-1 (N1), and 2 mg.l-1 (N1). If there is a difference in data analysis using the F test, then proceed with the BNT level test of 5%. Based on the research results obtained, the influence of TDZ growth regulators and no effect of the concentration of NAA growth regulator on stevia bud multiplication book number. There is an effect of TDZ on plantlet height, leaves, and stevia shoot multiplication nodes.